An education in impermanence: historical intermittency and Lessing's The Golden Notebook. Issue 5 (28th July 2016) - Darlington, Joseph
ABSTRACT: This paper seeks a reengagement with Doris Lessing's classic novel The Golden Notebook in relation to the concept of intermittency outlined in Andrew Gibson's recent theoretical work. Gibson argues that recent continental philosophy has broken with a linear reading of history in favour of the intermittent occurrence of Events: moments of crisis and rupture from which truth, politics, and justice emerge into the actual. Lessing's novel, praised for its honest depiction of women's experience at the dawn of the Sixties, is situated resolutely in a post-war world between Events, a time Gibson would depict as concrete in its non-Evental stasis. However, the vision of history which emerges in the novel is porous, ephemeral, one moment splintered between characters' contested ideologies and the next fused in bodily interpellation. By returning to this work of considerable historical significance we can also contest Gibson's categorisation of literature as a 'residue of events'. A paradigmatic rupture in the cultural framework forces a reengagement with the historical present with equal, if not superior force to the physical manifestation of the political. Lessing's novel, this paper argues, stages the Evental entrance of the permeable emotional body into a post-war British discourse dominated by 'managed' technocratic forms.